Neurodevelopment and Fetal Growth in Fetuses with Congenital Heart Disease: Perkembangan Saraf dan Pertumbuhan Janin dengan Penyakit Jantung Bawaan - Adhi Pribadi (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To determine mechanisms underlying fetal growth abnormalities, particularly intrauterine neurodevelopment, in congenital heart defects. Method: Literature Review Results: Since intrauterine, smart mechanisms have ensured that blood flow to the central nervous system remains smooth to maintain Neurodevelopment. The mechanism fluctuates to keep oxygen flowing to the brain. Blood with the highest oxygen content should always be pumped to upper body and the head via the heart and the aorta. Aortic arch region contains three major blood vessels, a.Brachiocephalic, a.Carotid communis, and a.Subclavia that bleed the upper body and head, including the brain. So, blood flow from the left heart through the aortic arch is critical for fetal brain growth. If the heart cannot drain blood to the head, brain growth will be jeopardized because hypoxia will interfere with brain growth so will be influence to Neurodevelopment. Impaired blood flow can occur as early as intrauterine, particularly if the fetus has congenital heart disease. Blood flow in the Middle Cerebral Artery (MCA) can be used to measure blood flow in the fetus head. The pulsatility index value can be used to measure blood flow in the MCA, and another parameter is the cardioplacental ratio. There is a decrease in flow to the head in congenital heart disease, which results in a decrease in the Pulsatily index of the MCA and a decrease in the cardioplacental ratio. Conclusions: Prolonged reduction in cardiac-derived blood flow leads to compromised neurodevelopment. Consequently, timely correction of postpartum heart defects becomes paramount to prevent protracted impairments in brain growth. Failing to address this promptly could also diminish the overall quality of life for children afflicted by congenital heart disease. Keyword: cardioplacental ratio, middle cerebral artery, congenital heart disease, fetal neurodevelopment. Keyword: cardioplacental ratio, cerebral media artery, congenital heart disease, fetal neurodevelopment. Abstrak Tujuan: Untuk menentukan mekanisme kelainan pertumbuhan janin terutama perkembangan saraf intrauterin pada cacat jantung bawaan. Metode: Kajian Pustaka Hasil: Pada kehidupan intrauterin, mekanisme yang baik telah memastikan bahwa aliran darah ke sistem saraf pusat tetap lancar untuk mempertahankan perkembangan saraf. Mekanisme ini berfluktuasi untuk menjaga oksigen tetap mengalir ke otak. Darah dengan kandungan oksigen tertinggi harus selalu dipompa ke otak melalui jantung dan arteri utama ke kepala melalui a.Brachiocephalic, a.Carotid communis, dan a.Subclavia. Pada daerah arkus aorta terdapat tiga pembuluh darah utama yang memperdarahi tubuh bagian atas dan kepala, termasuk otak. Aliran darah ini dipompa melalui jantung kiri melalui arkus aorta. Bila jantung tidak dapat mengalirkan darah ke kepala, maka akan menyebabkan pertumbuhan otak terancam karena hipoksia akan mengganggu pertumbuhan otak, sehingga secara jangka panjang akan berpengaruh terhadap perkembangan saraf fetus. Gangguan aliran darah dapat terjadi sejak dini terutama jika janin memiliki penyakit jantung bawaan. Aliran darah di Arteri Serebri Media (MCA) dapat digunakan untuk mengukur aliran darah pada bagian kepala. Nilai indeks pulsatilitas dapat digunakan untuk mengukur aliran darah di MCA, dan parameter lain adalah rasio kardioplasental. Terdapat penurunan aliran ke kepala pada penyakit jantung bawaan, yang mengakibatkan penurunan indeks Pulsatily pada MCA serta terdapat penurunan rasio kardioplasental. Kesimpulan: Penurunan perkembangan saraf terjadi ketika aliran darah dari jantung berkurang secara kronis ke daerah kepala janin, sehingga bila terdapat kelainan jantung bawaan pasca persalinan harus diperbaiki segera agar penurunan pertumbuhan otak pada periode pascasalin tidak berlangsung terlalu lama. Bila hal ini terjadi akan menurunkan pula kualitas hidup anak dengan penyakit jantung bawaan. Kata kunci: arteri serebri media, penyakit jantung bawaan, perkembangan saraf janin, rasio kardioplasenta.